A study of web services adoption in Singapore. - Seow, Poh Sun. (2008)
With the advent of Web Services in the last 18 months, discussions on the subject of Web Services have increased dramatically in the IT and business press. Many people in the IT industry are touting Web Services as the next big thing, creating a frenzy of hype around it. Conversely, others have questioned the promises of Web Services, labeling it as an over-hyped concept that remains more idea than substance. We believe that the reality probably lies somewhere in the middle.